2013
DOI: 10.1186/2193-1801-2-132
|View full text |Cite
|
Sign up to set email alerts
|

International student mobility and highly skilled migration: a comparative study of Canada, the United States, and the United Kingdom

Abstract: Against the backdrop of demographic change and economic reconfiguration, recruiting international students, especially those at tertiary level, has drawn growing attention from advanced economies as part of a broad strategy to manage highly skilled migration. This comparative study focuses on three English speaking countries receiving international students: Canada, the United States, and the United Kingdom. International student policies, in particular entry and immigration regulations, and the trends in stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 10 publications
0
38
0
1
Order By: Relevance
“…The vast majority of non‐European mobile students struggle with visa issues and lack of opportunities to gain valuable post‐study experience in the UK. She and Wotherspoon, (: 11) argued that this relatively high level of openness and control in managing international student mobility combined with the strategy to recruit international students, in particular from non‐EEA countries, is not well integrated into the UK's skilled immigration plan compared with other top receiving countries such as Australia, Canada and Japan, which might be seen as countries with a clear study to residence pathway. Countries like the United States, the United Kingdom, France and Germany are characterised by a more staggered and significantly more uncertain journey to permanent residency (Robertson, ; Liu‐Farrer, ).…”
Section: International Student Flows To the Ukmentioning
confidence: 99%
“…The vast majority of non‐European mobile students struggle with visa issues and lack of opportunities to gain valuable post‐study experience in the UK. She and Wotherspoon, (: 11) argued that this relatively high level of openness and control in managing international student mobility combined with the strategy to recruit international students, in particular from non‐EEA countries, is not well integrated into the UK's skilled immigration plan compared with other top receiving countries such as Australia, Canada and Japan, which might be seen as countries with a clear study to residence pathway. Countries like the United States, the United Kingdom, France and Germany are characterised by a more staggered and significantly more uncertain journey to permanent residency (Robertson, ; Liu‐Farrer, ).…”
Section: International Student Flows To the Ukmentioning
confidence: 99%
“…While some scholars have attempted to articulate the importance of student visa policies (Tremblay, ; Gribble, ; She and Wotherspoon, ), few offer systematic analyses of the content of the policies or the context under which these policies emerged and evolved (Robertson, ). This article attempts to address the lack of policy analysis and comparison within the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The global trend of student migration has led to extensive academic discussion, mainly focusing on students' motives and channels of migration, their acculturation in host societies and the effects of student migration on source and host societies (Bahna, ; Carlson, ; Collins, ; Collins, Ho, Ishikawa, & Ma, ; Fong, ; Waters, ). Recent research (Hawthorne, ; Kim, ; Li, ; Robertson, ; She & Wotherspoon, ; Yu, ) has shown that completing their studies does not mean the end of their migratory journey in the host society. In the context of global competition for skilled workers and talent, international students are considered potential skilled workers and are allowed to seek employment after graduation and even to explore settlement opportunities in many host societies (Hawthorne, ; Mosneaga & Winther, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars (Arthur & Flynn, ; Hawthorne, ; Kim, ; Moskal, ; Robertson, ) have examined how immigration policies and structural factors in host countries shape the opportunities and obstacles inherent in migrant students' transition to skilled employees. Others (Li, ; Mosneaga & Winther, ; She & Wotherspoon, ; Yu, ) have focused on migrant students' individual decisions and agency in seeking employment after graduation.…”
Section: Introductionmentioning
confidence: 99%